Understanding mental disorders : a philosophical approach to the medicine of the mind - Lafleur, Daniel; Mole, Christopher, 1979-; Onclin, Holly (Routledge, 2019)
Understanding Mental Disorders aims to help current and future psychiatrists, and those who work with them, to think critically about the ethical, conceptual, and methodological questions that are raised by the theory and practice of psychiatry. It considers questions that concern the mind's relationship to the brain, the origins of our norms for thinking and behavior, and the place of psychiatry in medicine, and in society more generally. With a focus on the current debates around psychiatry's diagnostic categories, the authors ask where these categories come from, if psychiatry should be looking to find new categories that are based more immediately on observations of the brain, and whether psychiatrists need to employ any diagnostic categories at all. The book is a unique guide for readers who want to think carefully about the mind, mental disorders, and the practice of psychiatric medicine.